Enhancing Biology Learning through 3D Models: A Study of Academic Performance in Nigerian Secondary Schools - Babalola, Ebenezer Omolafe; Omolafe, Eyiyemi Veronica (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Despite the recognized importance of Biology in secondary education, students' performance in the subject remains persistently low, particularly in Nigeria, due to the continued reliance on abstract, text-based instructional methods. This study addresses this pedagogical gap by evaluating the impact of a 3-Dimensional Model of the Human Circulatory System (3-DMHCS) on students' academic performance. Grounded in constructivist and multimodal learning frameworks, the study utilized a quasi-experimental post-test non-randomized control group design involving 60 students (49 from public and 11 from private schools). Participants were assigned to either a control group receiving conventional instruction or an experimental group taught using the 3-DMHCS. The Biology Performance Test (BPT), validated and yielding a reliability coefficient of 0.86 (KR-20), was used for assessment. Quantitative results revealed that the experimental group achieved a higher mean post-test score (M = 13.36, SD = 3.44) compared to the control group (M = 11.42, SD = 2.87), with a statistically significant mean difference of 1.94 (t(58) = 2.83, p < 0.01). Additionally, over 53% of students in the experimental group scored within the high range (16–20), whereas none in the control group reached this threshold. Notably, no significant difference was observed between public and private school students’ performance in the experimental group (t(58) = -0.180, p = 0.86), indicating the model’s equitable effectiveness across institutional contexts. The study contributes novel evidence on how low-cost, tactile instructional models can bridge educational disparities and enhance students' grasp of complex biological systems. It advocates for integrating 3D instructional tools into mainstream science curricula and underscores the need for professional development to support such pedagogical innovations.